P254 Secukinumab retention and safety in patients with active psoriatic arthritis or ankylosing spondylitis: two-year interim results of the observational SERENA study. (23rd April 2022) - Gaffney, Karl; Kiltz, Uta; Sfikakis, Petros; Gullick, Nicola; Theodoridou, Athina; Brandt-Juergens, Jan; Lespessailles, Eric; Fang, Juanzhi; Pournara, Effie; Schulz, Barbara; Jagiello, Piotr
Abstract: Background/Aims: SERENA is an ongoing, prospective, non-interventional study evaluating retention, effectiveness, safety/tolerability and quality of life in > 2, 900 patients with moderate to severe plaque psoriasis, active psoriatic arthritis (PsA) or active ankylosing spondylitis (AS) treated with secukinumab at 438 sites across Europe for up to 5 years. We present interim results reporting secukinumab treatment retention and safety data through two years in PsA and AS patients. Methods: This interim analysis presents data from 534 PsA and 470 AS patients enrolled (target population fulfilling eligibility criteria) and followed for at least two years. Patients (≥18 years) with active PsA or AS should have received at least 16 weeks secukinumab treatment before enrolment in the study. Retention rate was defined as percentage of patients who did not discontinue secukinumab treatment. Treatment break was defined as interruption of therapy for at least three months after last injection. Results: The mean treatment duration prior to enrolment in the study was 1.0 year and 0.91 year for PsA and AS, respectively. The retention rates for secukinumab after one year since enrolment and since initiation of treatment were: PsA, 85.2% (n = 519, CI: 82.01-88.32) and 96.8% (n = 528, CI: 95.18-98.38); AS, 85.8% (n = 452, CI: 82.52-89.17) and 94.2% (n = 464, CI: 91.94-96.42), respectively. After two years since enrolment and since initiation of treatment, the retention rates were: PsA, 74.9% (n = 498, CI: 70.99-78.81) and 87.0% (n = 515, CI: 83.99-89.99); AS, 78.9% (n = 437, CI: 75.01-82.88) and 84.8% (n = 454, CI: 81.39-88.21), respectively. At baseline, the majority of PsA (79.5%; n/N=423/532) patients were receiving secukinumab 300 mg, while 97.0% (n/N=456/470) of AS patients were receiving secukinumab 150 mg. The majority of patients continued their initial secukinumab dose; "no dose change" in secukinumab treatment was reported after one and two years in the study (year one: PsA, 93.4% [n = 499] and AS, 92.6% [n = 435]; year two: PsA, 89.7% [n = 479] and AS, 87.9% [n = 413]). Secukinumab treatment break was recorded for 31 PsA patients (median [min, max] treatment break duration in days: 125.0 [61-461]) and for 42 AS patients (118.0 [61-813]), mainly due to adverse events reported in 58.1% (n = 18) and 45.2% (n = 19) of patients, respectively. The retreatment started with monthly dosing in most of the cases: PsA, 80.6% (n/N=25/31) and AS, 76.2% (n/N=32/42). No new or unexpected safety signals were reported. Conclusion: Secukinumab retention rates in a real-world setting after more than two years since initiation of treatment and after two years since study enrolment indicate high persistence rates. Safety data collected prospectively for up to two years confirm the favorable safety profile of secukinumab. Disclosure: K. Gaffney: Consultancies; AbbVie, Celgene, Lilly, Pfizer, Gilead, MSD, Novartis, UCB. Member of speakers' bureau; AbbVie, Celgene, Lilly, Gilead, MSD, Novartis, UCB, Pfizer. Grants/research support; AbbVie, Celgene, Lilly, Pfizer, Gilead, MSD, Novartis, UCB. U. Kiltz: Consultancies; AbbVie, Biocad, Biogen, Chugai, Eli Lilly, Grünenthal, Hexal, Janssen, MSD, Novartis, Pfizer, Roche, UCB. Grants/research support; AbbVie, Biocad, Biogen, Chugai, Eli Lilly, Grünenthal, Hexal, Janssen, MSD, Novartis, Pfizer, Roche, UCB. P. Sfikakis: Consultancies; AbbVie, Amgen, Boehringer Ingelheim, Celgene, Eli-Lilly, Janssen, Novartis, Pfizer. Grants/research support; AbbVie, Amgen, Boehringer Ingelheim, Celgene, Eli-Lilly, Janssen, Novartis, Pfizer. N. Gullick: Consultancies; AbbVie, Celgene, Eli Lilly, Izana, Janssen, Novartis, UCB. Member of speakers' bureau; AbbVie, Celgene, Eli Lilly, Izana, Janssen, Novartis, UCB. Grants/research support; AbbVie, Celgene, Eli Lilly, Izana, Janssen, Novartis, UCB. A. Theodoridou: Consultancies; UCB, Amgen, Novartis. J. Brandt-Juergens: Consultancies; AbbVie, Pfizer, Roche, Sanofi-Aventis, Novartis, Lilly, MSD, UCB, BMS, Janssen, Medac. Member of speakers' bureau; AbbVie, Pfizer, Roche, Sanofi-Aventis, Novartis, Lilly, MSD, UCB, BMS, Janssen, Medac. E. Lespessailles: Consultancies; Amgen, Expanscience, Lilly, MSD. Member of speakers' bureau; Amgen, Expanscience, Lilly, MSD. Grants/research support; Abbvie, Amgen, Lilly, MSD, UCB, . J. Fang: Other; Employee of Novartis. E. Pournara: Shareholder/stock ownership; Novartis. Other; Employee of Novartis. B. Schulz: Other; Employee of Novartis. P. Jagiello: Other; Employee of Novartis.